IMPLEMENTING QUANTUM LEARNING BASED ON GROUP LEARNING IN IMPROVING EARLY CHILDHOOD LEARNING OUTCOMES - Zaenol Fajri; Uun Ayu Faradina (Raudhah - Proud To Be Professional, 2023)
Education is a method of acquiring knowledge in infancy. Early infancy is a beautiful age for the continuity of child growth and development that can never be replicated. Therefore, this growth and development process requires an educator's direction and guidance. One way an educator can aid in the growth and development of early childhood is by selecting models and learning strategies appropriate to students' talents, interests, and characteristics. A suitable learning model for early childhood is the quantum learning model, which employs group learning so that students complement and help each other in supporting aspects of child development. This research aimed to determine the effectiveness of group learning-based quantum learning in improving early childhood learning outcomes. The research method was descriptive and qualitative, with data collected through observation, interviews, and documentation. The research results were quite positive; learning activities were designed to be conducive and pleasurable so that children would be inspired to participate in learning at all times. This was characterized by an increase in the percentage of very well-developed children, reaching 38.89% from only 5.56% previously, developing as expected, coming to 44.44% from the initial percentage of 16.67, while the percentage of children starting to develop could be reduced from 44.44% to 11.11%. Undeveloped children decreased from 33.33% to 5.56%. As a result, it can be concluded that the implementation of group learning-based quantum learning is very suitable for early childhood in Pancasila Tamanan Kindergarten, as it can increase enthusiasm, a sense of excitement, motivation, interest, cooperation, mutual assistance, and respect, and can support the improvement of student learning outcomes.